Detection of Ralstonia solanacearum phylotype II, race 2 causing Moko disease and validation of genetic resistance observed in the hybrid plantain FHIA-21 - Pardo, Juan Manuel; López Alvarez, Diana; Ceballos, Germán; Álvarez, Elizabeth; Cuéllar, Wilmer Jose (Springer, 2019)
Vascular wilt of banana and plantains, also known as Moko disease, is caused by Ralstonia solanacearum (Rs) phylotype II, and is the main bacterial disease affecting these crops in the Americas. Upon comparative sequence analysis of 44 Rs genomes we developed an improved PCR protocol based on the nucleotide sequence of a gene coding for a hypothetical DUF3313 domain protein. Next, we tested the detection protocol with two Rs inoculation methods to validate field resistance reported in the hybrid plantain genotype FHIA-21, previously identified as susceptible to Moko disease in greenhouse experiments in which wounds were caused to the roots prior to inoculation. By using an inoculation method without causing wounds to the roots, we confirmed resistance of FHIA-21 to Moko disease (no Rs was detected by PCR in inoculated plants). In contrast, the field-susceptible genotype Dominico Hartón developed severe symptoms of Moko disease, regardless of the inoculation method used. FHIA-21 showed an area under the disease progress curve (AUDPC) close to zero, while Dominico Hartón plants showed AUDPC values ranging from 65.8 to 88.4. The availability and analysis of genomic data facilitates the development of improved pathogen detection tools that together with the availability of improved inoculation methods and tolerant genotypes to Moko disease will be of great use in Musa breeding programs.